Is Rice Improvement Still Making a Difference? Assessing the Economic, Poverty, and Food Security Impacts of Rice Varieties Released from 1989 to 2009 in Bangladesh, Indonesia and the Philippines - Raitzer, D.A.; Sparks, A.H.; Huelgas, Z.; Maligalig, R.; Balangue, Z.; Launio, C.; Daradjat, A.; Ahmed, H.U. (CGIAR Independent Science and Partnership Council, 2015)
This is one of the three proposals funded through a competitive call for proposals to evaluate the links between agricultural research and poverty in 2011. More background on the SPIA project (Social impacts: poverty and hunger http://impact.cgiar.org/impacts/poverty) can be found here (http://impact.cgiar.org/impacts/poverty).